2012
DOI: 10.1063/1.4710994
|View full text |Cite
|
Sign up to set email alerts
|

Porosity-induced relaxation of strains in GaN layers studied by means of micro-indentation and optical spectroscopy

Abstract: We report the fabrication of porous GaN nanostructures using UV-assisted electroless etching of bulk GaN layer grown on c-plane sapphire substrate in a solution consisting of HF : CH 3 OH : H 2 O 2 . The morphology of the porous GaN nanostructures was characterized for different etching intervals using high resolution scanning electron microscopy. The geometry and size of resultant pores do not appear to be affected by the etching time; however, the pore density was augmented for longer etching time. Micro-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…However, the compressive stress values in the literature for the as-grown and porous GaN prepared by the same method were evaluated to be 0.36 GPa and 0.27 GPa, respectively. 8 The compressive stress in the GaN NWs is lower than that in the asgrown sample due to the stress release. Furthermore, the residual strain, 3 xx , in the GaN NWs can be obtained using the expression s xx ¼ Mf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the compressive stress values in the literature for the as-grown and porous GaN prepared by the same method were evaluated to be 0.36 GPa and 0.27 GPa, respectively. 8 The compressive stress in the GaN NWs is lower than that in the asgrown sample due to the stress release. Furthermore, the residual strain, 3 xx , in the GaN NWs can be obtained using the expression s xx ¼ Mf.…”
Section: Resultsmentioning
confidence: 99%
“…It is a prime candidate for use in future high-performance, high power optoelectronic devices. [7][8][9] Singlecrystalline GaN NWs and nanotubes are promising for realizing photonic and biological nanodevices such as blue-light emitting diodes (LEDs), short-wavelength ultraviolet nanolasers, 10,11 and nanouidic biochemical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…It is recently reported that mechanical stress engineering by controlling sapphire substrate thickness may reduce the piezoelectric field within the InGaN active layer and thus enhance the green light emission . It is also demonstrated that porous GaN templates reduce the misfit strain and improve the luminescence property of InGaN/GaN QWs on them . These achievements indicate that a more mechanical compliant GaN template will greatly benefit the light emission, which stimulates many researchers to design and fabricate improved GaN template.…”
Section: Introductionmentioning
confidence: 97%
“…Several methods have been reported for synthesizing SiNWs, including chemical vapor deposition (CVD), 17 laser ablation, 18 physical vapor deposition (PVD), 19 ... Among these, wet electroless etching [20][21][22] has been widely used as an alternative top-down route in the cell fabrication process.…”
Section: Introductionmentioning
confidence: 99%